A novel ferritin L (FerL) in hybrid crucian carp could participate in host defense against Aeromonas hydrophila infection and diminish inflammatory signals. Issue 120 (January 2022) - Xiong, Ning-Xia; Ou, Jie; Li, Shi-Yun; Zhao, Jia-Hui; Huang, Jin-Fang; Li, Ke-Xin; Luo, Sheng-Wei; Liu, Shao-Jun; Wen, Ming; Wu, Chang; Wang, Shi; Luo, Kai-Kun; et al.
Abstract: FerL, a multifunctional iron-storage polypeptide, not only exhibited a regulatory role in iron metabolism, but also participated in the regulation of fish immunity. In this study, ORF sequence of WR-FerL was 522 bp, encoding 173 amino acid residues. Tissue-specific analysis revealed that the highest expression of WR-FerL was detected in spleen. A. hydrophila challenge and LPS stimulation could sharply enhance WR-FerL mRNA expression in tissues and fish cells, respectively. Purified WR-FerL fusion peptide exhibited in vitro binding activity to A. hydrophila and endotoxin, limited bacterial dissemination to tissues as well as attenuated A. hydrophila -induced production of pro-inflammatory cytokines. Moreover, WR-FerL overexpression could abrogate NF-κB and TNFα promoter activity in fish cells. These results indicated that WR-FerL could play an important role in host defense against A. hydrophila infection. Highlights: A novel FerL gene was characterized in hybrid crucian carp. A. hydrophila challenge and LPS stimulation could increase expressions of WR-FerL mRNA. WR-FerL could elicit a binding activity to A. hydrophila and LPS.